2012
DOI: 10.1021/bi201457u
|View full text |Cite
|
Sign up to set email alerts
|

DnaK Prevents Human Insulin Amyloid Fiber Formation on Hydrophobic Surfaces

Abstract: We have developed a multiwell-based protein aggregation assay to study the kinetics of insulin adsorption and aggregation on hydrophobic surfaces and to investigate the molecular mechanisms involved. Protein-surface interaction progresses in two phases: (1) a lag phase during which proteins adsorb and prefibrillar aggregates form on the material surface and (2) a growth phase during which amyloid fibers form and then are progressively released into solution. We studied the effect of three bacterial chaperones,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…As shown before [6], the LVEALYL peptide accelerates HI aggregation kinetics at pH 7.3 and 37°C, only in the presence of hydrophobic surfaces (polystyrene) but not in the presence of PEG-coated surfaces preventing HI binding. The maximum effect is observed at a peptide concentration of 8.6 lM, and the lag time is reduced by 66% on average ( Table 1).…”
Section: The Lvealyl Peptide Accelerates Hi Aggregation Kinetics Whensupporting
confidence: 69%
See 1 more Smart Citation
“…As shown before [6], the LVEALYL peptide accelerates HI aggregation kinetics at pH 7.3 and 37°C, only in the presence of hydrophobic surfaces (polystyrene) but not in the presence of PEG-coated surfaces preventing HI binding. The maximum effect is observed at a peptide concentration of 8.6 lM, and the lag time is reduced by 66% on average ( Table 1).…”
Section: The Lvealyl Peptide Accelerates Hi Aggregation Kinetics Whensupporting
confidence: 69%
“…In this study, we show that the LVEALYL peptide, adsorbed on hydrophobic surfaces at sub‐stoichiometric concentrations, favors HI binding and the formation of HI amyloidal fibers. We previously showed that HI adsorbed on hydrophobic surfaces exposes a motive containing the LVEALYL peptide, which is recognized by the DnaK/DnaJ bacterial chaperones [6]. Combining these two observations indicates how HI amyloidal aggregates form on hydrophobic surfaces.…”
Section: Discussionmentioning
confidence: 84%
“…The binding sites of antibiotics on insulin amyloids remain unclear. The stacked β-sheet structure of insulin amyloids contains hydrophobic residues 33 , and minocycline could bind to hydrophobic sites 34 . Thus, a possible hypothesis is that the binding site of minocycline is the stacked β-sheet structure.…”
Section: Identification Of the Binding Site Of Minocycline In Insulinmentioning
confidence: 99%
“…35 The latter is the case, for instance, of hydrophobic surface-induced amyloid fibrillation of insulin. 36,37 In this case, adsorbed proteins form clusters (nuclei) on the surface which, at a critical size, induce the growth of surface-bound amyloid fibers. Upon agitation, such protein aggregates can be released in solution which can trigger further surface aggregation and sometimes aggregate growth in solution.…”
Section: Aggregation Statementioning
confidence: 99%